Is the Boom in the Residential Real Estate Development Sector in Poland Ending? - Siemińska, Ewa Hanna; Krajewska, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The business activity of real estate development companies depends on very many macro as well as micro factors. The main determinants of their operation on the real estate market include those of a supply-demand as well as institutional-legal nature. In practice, it turns out, however, that even in the case of excellent financial and sales results for at least a few years, they are faced with increasingly large problems and limitations, which first influence a decrease in growth rate, and later can be a source of problems with financial liquidity. The aim of the work is to identify the most important current determinants connected with the business activity of real estate development companies, accounting for both regulatory as well as market risks. A study states that in 2017–2018, conditions of management in the housing sector have changed and symptoms of their deterioration are visible. The results of the carried out analyses indicate that the investment boom and very favorable climate for carrying out activities connected with real estate development, especially on the housing market, which has been around since at least 2015, began to show increasingly clearer symptoms indicating a halt in the growth rate and a worsening situation of real estate developers at the beginning of 2018. The applied research methods include a study of the source literature and current legal regulations, as well as the analysis of statistical and financial data derived from rich, both primary and secondary empirical databases. The financial data used in the study relate primarily to the leading development companies listed on the Warsaw Stock Exchange.